The Influence of Celebrity Endorsement, Product Quality and Price on Purchase Interest of Kanzler Single Sausage Products - Evelyn Maurencia; Hery Winoto Tj; Soegeng Wahyoedi (SIASAT, 2021)
At this time, technological advances are increasingly having a strong enough impact and if it can be utilized properly, this maximizes the results obtained from the existence of the technology itself. Especially in the act of marketing an item, using social media that has many users will make the product marketing process much easier. Supported by the current pandemic conditions that have made major changes in purchasing and selling product transactions, as well as a fairly high increase in internet users. Therefore, using social media that displays advertisers in the form of videos will be considered effective. For now, people are starting to be presented with various types of social media featuring videos such as Youtube, Snapchat, Instagram & TikTok. According to research (OGUNSIJI, 2012) celebrity endorsement is a marketing tool created to show differentiation points between various brands and coverage in the market. Meanwhile, (Nelson & Gloria, 2012) focuses celebrity support on a global perspective because this is a communication strategy that will create promotional actions for a product in the form of goods and services in society. The right choice should be made to choose a celebrity to endorse a brand, as celebrity endorsement can affect the image and productivity of an organization in positive or negative ways. With this research, it is hoped that entrepreneurs who want to market their products will be wiser and easier in choosing what kind of media are currently having a high appeal to consumers. In addition, readers will also be invited to see the benefits of the impact of celebrity endorsement, the quality of a product and how the price affects consumer purchase interest.